f1(1285) formation in two-photon collisions at LEP - Dova, María Teresa (2001)
The ηπ+π− final state in two-photon collisions is studied with the L3 detector at LEP, at centre-of-mass energies from 183 to 209 GeV with an integrated luminosity of 664.6 pb−1. The f1(1285) meson is observed and the Q2 dependence of its production is compared to different form factor models. The γ γ -coupling parameter Γ γ γ is found to be 3.5 ± 0.6(stat.) ± 0.5(sys.) keV. The branching fraction Γ (f1(1285) → a0π )/Γ (f1(1285) → ηππ) is also measured.